Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Simplify the first inequality.
Multiply 1/2 by x to get (1/2)x.
y≤(1/2)x+6 and y>−3x−1
Simplify.
y≤x/2+6 and y>−3x−1
Since x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.
x/2+6≥y and y>−3x−1
Because 6 does not contain the variable to solve for, move it to the right-hand side of the inequality by subtracting 6from both sides.
x/2≥−6+y and y>−3x−1
Multiply both sides of the equation by 2.
x≥−6⋅(2)+y⋅(2) and y>−3x−1
Multiply −6 by 2 to get −12.
x≥−12+y⋅(2) and y>−3x−1
Multiply y by 2 to get y(2).
x≥−12+y(2) and y>−3x−1
Multiply y by 2 to get y⋅2.
x≥−12+y⋅2 and y>−3x−1
Move 2 to the left of the expression y⋅2.
x≥−12+2⋅y and y>−3x−1
Multiply 2 by y to get 2y.
x≥−12+2y and y>−3x−1
Reorder −12 and 2y.
x≥2y−12 and y>−3x−1
Simplify the second inequality.
Because x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.
x≥2y−12 and −3x−1<y
Since −1 does not contain the variable to solve for, move it to the right-hand side of the inequality by adding 1 to both sides.
x≥2y−12 and −3x<1+y
Divide each term in the inequality by −3. When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign.
x≥2y−12 and −3x/−3>1/−3+y/−3
Cancel 3 in the numerator and denominator.
x≥2y−12 and −(−1⋅x)>1/−3+y/−3
Multiply −1 by x to get −1x.
x≥2y−12 and −(−1x)>1/−3+y/−3
Rewrite −1x as −x.
x≥2y−12 and −(−x)>1/−3+y/−3
Simplify
x≥2y−12 and x>−1/3+y/−3
x≥2y−12 and x>−1/3−y/3
Point of intersection: (-2, 5)
Multiply 1/2 by x to get (1/2)x.
y≤(1/2)x+6 and y>−3x−1
Simplify.
y≤x/2+6 and y>−3x−1
Since x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.
x/2+6≥y and y>−3x−1
Because 6 does not contain the variable to solve for, move it to the right-hand side of the inequality by subtracting 6from both sides.
x/2≥−6+y and y>−3x−1
Multiply both sides of the equation by 2.
x≥−6⋅(2)+y⋅(2) and y>−3x−1
Multiply −6 by 2 to get −12.
x≥−12+y⋅(2) and y>−3x−1
Multiply y by 2 to get y(2).
x≥−12+y(2) and y>−3x−1
Multiply y by 2 to get y⋅2.
x≥−12+y⋅2 and y>−3x−1
Move 2 to the left of the expression y⋅2.
x≥−12+2⋅y and y>−3x−1
Multiply 2 by y to get 2y.
x≥−12+2y and y>−3x−1
Reorder −12 and 2y.
x≥2y−12 and y>−3x−1
Simplify the second inequality.
Because x is on the right-hand side of the equation, switch the sides so it is on the left-hand side of the equation.
x≥2y−12 and −3x−1<y
Since −1 does not contain the variable to solve for, move it to the right-hand side of the inequality by adding 1 to both sides.
x≥2y−12 and −3x<1+y
Divide each term in the inequality by −3. When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign.
x≥2y−12 and −3x/−3>1/−3+y/−3
Cancel 3 in the numerator and denominator.
x≥2y−12 and −(−1⋅x)>1/−3+y/−3
Multiply −1 by x to get −1x.
x≥2y−12 and −(−1x)>1/−3+y/−3
Rewrite −1x as −x.
x≥2y−12 and −(−x)>1/−3+y/−3
Simplify
x≥2y−12 and x>−1/3+y/−3
x≥2y−12 and x>−1/3−y/3
Point of intersection: (-2, 5)
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.